The Impregnable Composition Writing Competency and Teaching Writing Methodologies - Gepila Jr, E C (KnE Social Sciences, 2018)
This study evaluated the composition writing competency of the Grade 7 students and focused on the following: teaching writing method/s used in the classroom; execution of the writing methods; composition writing competency of the PUP Laboratory High School grade seven students; and common errors PUP Laboratory High School grade seven students committed in composition writing. It used Descriptive Method in Quantitative-Qualitative Approach. A writing test was used in this study. These were written using two styles such as: Free Writing Style and Guided Writing Style, and were checked by the three (3) seasoned English teachers. The findings revealed that the only teaching writing method used in the classroom is the combination of Process and Genre Methods; composition writing competency of the PUP Laboratory High School seniors in all writing styles in terms of: Content, Thesis Statement, Organization, and Language Use and Editing are rated Very Good to Good. The researcher concluded that the compositions still need substantiation, well-defined introduction and conclusion, and zero error in mechanics and grammar though such are rated Good to Very Good. Keywords: Writing, Testing Writing, Teaching Writing, Polytechnic University of the Philippines